THE IMPACT OF SOME REVENUE INDICATORS ON THE GROSS DOMESTIC PRODUCT IN IRAQ FOR THE PERIOD (2005-2021) USING THE LOGARITHMIC FUNCTION - Wisam Ahmed Askar Taha; Abdullah Zaidan Khalaf Abdullah (Scholars Digest Publishing, 2024)
Economic literature indicates the existence of a reciprocal, meaningful relationship between revenues and Gross Domestic Product (GDP) in Iraq. Therefore, the study aims to analyze the evolution of revenues and the actual situation of GDP and measure the impact of revenues on GDP in Iraq for the period (2005-2021). The research was based on the hypothesis that there is a reciprocal and meaningful relationship between revenues and GDP in Iraq using the logarithmic function. The research concludes that an increase in oil revenues by one unit, while holding other factors constant, will contribute to an increase in GDP by (0.211) million dinars. An increase in tax revenues by one unit, while holding other factors constant, will contribute to an increase in GDP by (0.152) million dinars. An increase in other revenues by one unit, while holding other factors constant, will contribute to an increase in GDP by (0.073) million dinars. The research recommends increasing sources of financing for the general budget such as tax revenues, commodity revenues, and other revenues to finance and cover production or investment expenses.
Keywords: revenue indicators, Gross Domestic Product, logarithmic function.